PENINGKATAN KESIAPAN KERJA MELALUI PELATIHAN INTERVIEW DAN PENYUSUNAN CV BAGI FRESH GRADUATE DI KOTA TANGERANG - Eneng Wiliana; Nining Purwaningsih; Mahmudin Mahmudin (JPMUJ, 2026)
The increasingly competitive labor market requires fresh graduates to possess adequate work readiness skills, particularly in preparing curriculum vitae (CV) and facing job interviews professionally. However, many fresh graduates still experience difficulties in presenting their competencies through CV writing and interview communication. This community service activity aimed to improve work readiness among fresh graduates through interview training and professional CV preparation in Tangerang. The methods used in this activity included counseling, training, direct practice, interview simulations, and mentoring. The activity involved 35 participants consisting of fresh graduates who were preparing to enter the workforce. The implementation stages included preliminary observation, preparation of training materials, delivery of materials, CV writing practice, interview simulations, evaluation, and mentoring. The results of the activity showed that participants experienced increased understanding regarding professional CV preparation, interview techniques, communication skills, and self-confidence in facing recruitment processes. Participants were also able to improve the structure and content of their CVs according to industry standards. Interview simulations provided practical experience that helped participants answer questions more systematically and confidently. This activity contributed positively to improving participant employability skills and work readiness in facing increasingly competitive labor market conditions. Therefore, interview and CV training activities are considered effective in supporting the development of human resources among fresh graduates in Tangerang.